Development of potential biodiesel from agricultural wastes - Farra Diana, Binti Shahrom (Universiti Malaysia Sarawak (UNIMAS), 2012)
Biomass in the form of agricultural waste is believed to have potential in producing biodiesel. In this project, palm oil mill effluent (POME) wastes were used. The wastes were obtained from the cooling pond of Bau Palm Oil Mill (BAPOM), Sarawak. The wastes were undergoing transesterification in the presence of methanol and catalysts. Two types of catalysts were introduced which are heterogeneous and homogeneous base catalysts. The use of homogeneous base catalyst made the POME biodiesel existed in flakes-form and difficult to be purified. The percentages yield is 2.2% by weight. However, biodiesel which used heterogeneous base catalyst were produced in liquid-form and easy to be purified. The percentages yield is 23% by weight. The biodiesel were analyzed using several tests such as Fourier Transform Infrared (FTIR) Spectrometer, Gas Chromatography Mass Spectrometer (GC-MS) as well as physical tests like odour, viscosity and colour. From the analysis, it is proved that the biodiesel from POME had some fuel properties such as low acidity, viscosity and water content. Thus, it has the potential to become one of the energy sources in substituting diesel.